2020
DOI: 10.3390/min10060500
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Rare Earth Elements (Sc, Y, La, Ce, Nd, Sm) in Bauxite Residue (Red Mud) Obtained by Water and Alkali Leaching of Bauxite Sintering Dust

Abstract: One of the potential sources of rare-earth elements (REE) is the industrial waste known as red mud (bauxite residue), in which the majority of REE from the initial bauxite are concentrated via the Bayer process. Therefore, the studies of the subject, both in Russia and outside, focus almost exclusively on red mud processing. This article looks into the possibility of REE concentration into red mud by leaching an intermediate product of the bauxite sintering process at Russian alumina refineries, namely electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
1
11
0
2
Order By: Relevance
“…According to the EPMA analysis of RMF (Figure 2) and our previous research [43], it was found that the association of Sc with iron-containing minerals is high. After alkalifusing of bauxite followed by water leaching, the hematite matrix was destroyed, and the amount of the hydrosodalite was very low (Table 1, Figure 1).…”
Section: Study Of the Kinetics And Mechanism Of Sc Leaching From Rmfmentioning
confidence: 69%
“…According to the EPMA analysis of RMF (Figure 2) and our previous research [43], it was found that the association of Sc with iron-containing minerals is high. After alkalifusing of bauxite followed by water leaching, the hematite matrix was destroyed, and the amount of the hydrosodalite was very low (Table 1, Figure 1).…”
Section: Study Of the Kinetics And Mechanism Of Sc Leaching From Rmfmentioning
confidence: 69%
“…Coating technology opens the door for applications in pigment areas using Ti as pigment ion. Red mud could be used as a coating by thermal plasma spray technologies for wear resistance coating or corrosive resistance coating layers that could stand as a barrier against environmental conditions [ 81 , 82 , 83 ]. Coatings based on red mud offer an important erosion wear resistance, which can further be improved.…”
Section: Fields Of Application Of Red Mudmentioning
confidence: 99%
“…An electrostatic precipitator captured the tiniest particles (less than 20 µm) from the exhaust gases. The ESP dust chemical and phase compositions were shown in a previous research [28]. The ESP dust water leaching was carried out by distilled water at a temperature of 95 • C, L/S ratio of 10:1, and leaching time of 60 min.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…In this paper, we aim to evaluate the MgSO 4 leaching of Sc and other REEs from the RM obtained by water-alkali leaching of the sintering process dust that was performed in our previous research [28]. This RM contains up to 240 mg kg −1 Sc and a high amount of other REEs (up to 3200 mg kg −1 ) that have been released from the iron minerals solid matrix during the sintering process.…”
Section: Introductionmentioning
confidence: 99%